Fungsi komunikasi dan motivasi pengguna tanda tagar (#) di media sosial Indonesia - Muchamad Rudi Cahyono (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
In 2020 many hashtag (#) became trends, based on itâ€™s popularity and topics. The social media, hastags has several common functions such as promotion tools, trending boosters or to establish any agenda. The purpose of this research is to see the communication function and the motivation for using hashtags in Indonesia. This research was using content analysis to interpret deeper meaning a content and literature studies. Object of the reseacrh itsokaytonotbeokay was taken from populer hashtags or those that were widely used during 2020. #gagalkanomnibuslaw #fotoprofilbaru and #itsokaytonotbeokay entered the top 10 popular hashtag in 2020 released by Twitter Indonesia. The results of this study are the use of hashtags in Indonesia in 2020 shows the communication function and general motivation of hashtags, namely categorizing and organizing uploads to be on the same topic. More specifically to gather votes, information, comments into one important topic. Hashtags become an excuse to show themselves to the public and join popular groups, as well as add metadata to summarize information and design (beautify) posts. The marketing and branding functions are less than optimal when using the tailing function, but can be maximized if the hashtag is in accordance with the context. Hashtags in Indonesia are also widely used for activities to spread propaganda, attitudes, opinions, discourses to movements.Â